Vertical Handover Decision Processes for Fourth Generation Heterogeneous Wireless Networks - Al-Khalid, Hj Othman; Mahmood, Adnan; Hushairi, Zen (Asian Online Journals, 2013)
The increased growth in consumer demand for seamless access to communication services anywhere and anytime is inevitably driving an accelerated technological development towards the integration of an assortment of wireless network technologies – nowadays referred to as ‘Fourth Generation (4G) Wireless Systems’. In a typical 4G networking scenario, mobile terminals (MTs) with multiple interfaces are able to choose the most pertinent access links among the accessible substitutes [i.e. IEEE 802.11 WLANs, IEEE 802.16 WiMAX, satellite systems, bluetooth, etc. in addition to the traditional cellular telephony networks]. Thus to achieve seamless mobility and the requisite Quality of Service (QoS) in such a diverse environment, efficient ‘Vertical Handover Decision (VHD)’ algorithms needs to be designed in order to avert any degradation of services, reduction in throughput, increase in blocking probability and packet loss caused due to the unnecessary handovers, handover failures and connection breakdowns. This paper intends to present a comprehensive survey of VHD algorithms designed to satisfy these requirements. To offer a systematic comparison and thus to assess the tradeoffs between their complexity of implementation and efficiency, our study has categorized algorithms into various groups based on the main handover decision criterion used. The survey revealed that the currently proposed VHD algorithms either lacked a comprehensive consideration of several network parameters or studies’ reporting these problems lacks sufficient detail for implementation.